(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: The results of the fourth objective of the research on the care of transgender adolescents in secondary school are presented. This objective seeks to identify the main strengths and challenges of the Counseling professional in caring for transgender students. Methodology: The research was based on the naturalistic paradigm, using a qualitative approach and the phenomenological method. Semi-structured interviews were conducted with nine participants to collect the information (two counselors, two trans and cisgender students, one parent of the trans student, and two teachers). The analysis was conducted through triangulation between the interviews, theory, and guiding criteria, utilizing categorization and open coding to group the units of meaning into two analytical categories: strengths and challenges in the counseling intervention. Results: Respect, empathy, assertiveness, and confidentiality were identified as strengths. Regarding challenges, a lack of training on sexual diversity and tools for serving trans students was noted. Conclusions: The purpose emphasizes the need to enhance professional development and training on topics related to sexual diversity and inclusive sexuality education models. It also highlights the importance of inter-institutional coordination to strengthen care for transgender people in secondary school. A human rights-based approach and ongoing professional development are recommended to ensure safe educational environments for transgender people in their identity development.